Identification, characterization and expression analysis of biglycan in Asian elephant (Elephas maximus) - Siriwadee Chomdej (2018)
© 2017, Veteriner Fakultesi Dergisi. All rights reserved. The aims of this study were to investigate the coding sequence and the deduced amino acid sequence of Asian elephant’s biglycan gene as well as its expression in different tissues and conditions using wound healing as a model. The results showed that Asian elephant biglycan coding sequence was 1,110 base pair (bp) long (accession number: JQ753329), encoding 369 amino acids. The coding and amino acid sequences between Asian and African elephants revealed 99% and 98% similarity, respectively. The conserved domains of biglycan protein were also observed. In addition, its expression was found in 15 tissues with a predominant expression in cartilage and spleen. For expression analysis in the wound healing process, it was found that the level of biglycan mRNA was influenced by many factors, including age, type of wound and stage of wound healing.